How to Design a Fiscal Strategy in a Resource-Rich Country : Guidance Note on the Excel Template (v1.0). (IMF How To Notes; How-To Note ;, 2021)
This guidance note describes how to use the Excel-based template developed by the Fiscal Affairs Department (FAD) of the IMF accompanying the note 'How to Design a Fiscal Strategy in a Resource-Rich Country.' This template uses data inputs to generate simulations of fiscal policy dynamics. It helps IMF teams and country authorities in RRCs analyze trade-offs associated with alternative fiscal strategies for the use of public resource wealth. Visualizing these trade-offs and assessing their sensitivity to underlying macroeconomic assumptions can help inform policymakers on the most appropriate fiscal strategy, given country-specific circumstances.